Domestication and Re-creation of Poetic Style: A Study of Tamil Translations in Selected Poems in English by Prof. S. Sriskandarajah - Pavithra, S.; Kannathas, K. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
This study examines the stylistic and cultural transformation of English poetry in Tamil translation through the lens of Lawrence Venuti’s theory of domestication, with specific reference to the Tamil translations by Prof. S. Sriskandarajah in his bilingual collection “Selected Poems in English”. The source texts, written by various English poets, often contain culturally embedded imagery, metaphor and rhythm that are intricately tied to the English literary tradition. This research investigates how these poetic elements are adapted into Tamil, a language with its own distinct aesthetic and literary conventions by focusing on a selection of culturally oriented poems. Using a descriptive and comparative methodology, the analysis identifies how key stylistic devices such as tone, diction, allusion, and figurative language are altered or restructured in the target texts. Drawing on Venuti’s concept of domestication, the study argues that the translator intentionally privileges fluency and cultural proximity in the Tamil versions, aiming to create a sense of naturalness and immediacy for the Tamil reader. The translations are viewed not as literal equivalents but as poetic recreations that maintain the emotional depth and thematic integrity of the originals while embedding them in the familiar cultural and linguistic frameworks of the Tamil literary tradition. By foregrounding domestication as a strategic and stylistic choice, the study positions the translator as a cultural mediator who negotiates between fidelity to the source and resonance with the target audience. The findings suggest that domestication facilitates the recontextualization of foreign poetic texts into a Tamil worldview, enabling cross-cultural literary transmission without alienation. This research contributes to literary translation studies by demonstrating how domestication can serve not only as a tool for accessibility but also as a form of creative engagement that enriches both source and target literary traditions.
Keywords: Bilingual poetry; Cross-cultural transmission; Cultural adaptation; Domestication; Figurative language